2003
DOI: 10.1038/nn1088
|View full text |Cite
|
Sign up to set email alerts
|

Robust neural integration from retinal transplants in mice deficient in GFAP and vimentin

Abstract: With recent progress in neuroscience and stem-cell research, neural transplantation has emerged as a promising therapy for treating CNS diseases. The success of transplantation has been limited, however, by the restricted ability of neural implants to survive and establish neuronal connections with the host. Little is known about the mechanisms responsible for this failure. Neural implantation triggers reactive gliosis, a process accompanied by upregulation of intermediate filaments in astrocytes and formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
165
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(175 citation statements)
references
References 38 publications
7
165
0
3
Order By: Relevance
“…In an animal model of retinal degeneration both subretinal and intravitreal stem cell transplantation resulted in strong reactive gliosis and chondroitin sulfate proteoglycan deposition limiting stem cell migration into the host tissue 4, 5, 8, 12. This effect appeared to be independent of the type and origin of stem cells transplanted and, consistent with our study, was observed with both heterologous and autologous stem cell sources including Muller stem cells 12, photoreceptor precursors 5, neuronal progenitors 9, induced pluripotent stem cells 10, 11, and MSCs 4, 39. Here, we offer a detailed investigation of retina glial responses to intravitreal BM‐MSC transplantation in order to identify molecular mechanisms behind graft‐induced reactive gliosis in the retina.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In an animal model of retinal degeneration both subretinal and intravitreal stem cell transplantation resulted in strong reactive gliosis and chondroitin sulfate proteoglycan deposition limiting stem cell migration into the host tissue 4, 5, 8, 12. This effect appeared to be independent of the type and origin of stem cells transplanted and, consistent with our study, was observed with both heterologous and autologous stem cell sources including Muller stem cells 12, photoreceptor precursors 5, neuronal progenitors 9, induced pluripotent stem cells 10, 11, and MSCs 4, 39. Here, we offer a detailed investigation of retina glial responses to intravitreal BM‐MSC transplantation in order to identify molecular mechanisms behind graft‐induced reactive gliosis in the retina.…”
Section: Discussionsupporting
confidence: 88%
“…However, one of the unaddressed obstacles is the gliotic response that astrocytes and Muller glia (non‐neuronal support cells within the retina) exhibit in response to grafted cells 4, 5, 6. In retinal cell neuroprotection and replacement therapy, the glial response to the donor cell graft is an important barrier to overcome in order to enhance synaptic plasticity and axonal remodeling of surviving neurons as well as integration of a variety of donor cell types into the host retinal circuitry 4, 5, 7, as shown in the outer 5 and inner retina 4, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various techniques have been performed to promote the neuronal integration between the transplant and the host retina (Kinouchi et al, 2003;Lavik et al, 2005), no clear evidence of functional synaptic connectivity has yet been published. However, preliminary data from our group have shown that neurons in the transplant can be trans-synaptically labeled from the visually responsive site in the SC (Seiler et al, 2005b; manuscript submitted).…”
Section: Discussionmentioning
confidence: 99%
“…GFAP -/-Vim -/-mice show slower wound healing and reduced glial scaring after brain or spinal cord trauma (105). The Pekny group and others have previously reported improved regeneration in GFAP -/-Vim -/-mice, specifically axonal regeneration (106), (107), survival and integration of neuronal grafts in the retina (108) or improved synaptic regeneration in the denervated dentate gyrus of the hippocampus (109), for a review see (102).…”
Section: Reactive Astrocytesmentioning
confidence: 99%